“Omics” Tools for Better Understanding the Plant–Endophyte Interactions - Kaul, Sanjana; Sharma, Tanwi; K. Dhar, Manoj (Frontiers in Plant Science, 2016)
Endophytes, which mostly include bacteria, fungi and actinomycetes, are the endosymbionts that reside asymptomatically in plants for at least a part of their life cycle. They have emerged as a valuable source of novel metabolites, industrially important enzymes and as stress relievers of host plant, but still many aspects of endophytic biology are unknown. Functions of individual endophytes are the result of their continuous and complex interactions with the host plant as well as other members of the host microbiome. Understanding plant microbiomes as a system allows analysis and integration of these complex interactions. Modern genomic studies involving metaomics and comparative studies can prove to be helpful in unravelling the grey areas of endophytism. A deeper knowledge of the mechanism of host infestation and role of endophytes could be exploited to improve the agricultural management in terms of plant growth promotion, biocontrol and bioremediation. Genome sequencing, comparative genomics, microarray, next gen sequencing, metagenomics, metatranscriptomics are some of the techniques that are being used or can be used to unravel plant endophyte relationship.The modern techniques and approaches need to be explored to study endophytes and their putative role in host plant ecology. This review highlights “omics” tools that can be explored for understanding the role of endophytes in the plant microbiome. Keywords: Endophytism, microbiome, endophytes, genomics, metagenomics